Enhancing Public Financial Transparency Through the Integration of Taxation, Accounting, and Social Welfare Systems - Sulvariany Tamburaka; Nasrullah Dali (UIN Sunan Gunung Djati, 2024)
This study explores the impact of taxation, accounting, and social welfare system integration on public financial transparency in Indonesia. The study collected data from government reports and interviews with financial policy experts, auditors, and government officials using mixed methods, including quantitative and qualitative analysis. The analysis results show that system integration significantly improves transparency through more accurate fiscal reporting and better access to public financial information. Challenges such as technology implementation costs, bureaucratic resistance, and capacity gaps still hamper the integration process. These findings align with existing literature, which underlines the importance of political support and capacity building to overcome these obstacles. This study recommends better training and international support to support system integration efforts and improve accountability and public trust in state financial management.